A 71-Year-Old Man From Ecuador With a History of Type 2 Diabetes Mellitus and Severe COVID-19 Pneumonia and Lung Cavitation Associated With Triple Infection With Trichosporon Asahii, Klebsiella Pneumoniae, and Pseudomonas Aeruginosa. (November 2022) - Briones-Claudett, Killen H.; Briones-Claudett, Mónica H.; Cordova Loor, Francisco Javier; Murillo Vasconez, Roger Alexander; Rivera Salas, Carolina del Rosario; Bajaña Huilcapi, Cynthia K.; Estupinan Vargas, Domenica F.; Rodriguez Garcia, Stalin E.; Benitez Sólis, Jaime; Briones Zamora, Killen H.; Briones Marquez, Diana C.; Grunauer, Michelle
Unvaccinated patients with comorbidities that impair the immune function, such as type 2 diabetes mellitus, are more likely to develop severe COVID-19. The COVID-19-associated acute respiratory distress syndrome has raised new concerns in intensive care units globally owing to the presence of secondary fungal infections. We report the case of a 71-year-old man from Ecuador with a history of type 2 diabetes mellitus, severe COVID-19 pneumonia, and lung cavitation associated with triple infections with Trichosporon asahii, Klebsiella pneumoniae, and Pseudomonas aeruginosa . The patient with a history of high blood pressure and type 2 diabetes was admitted to our hospital from a private care center with a diagnosis of COVID-19-associated acute respiratory distress syndrome. On arrival, the patient presented with signs of hypoxemic respiratory failure. During his stay at another hospital, he had received tocilizumab and corticosteroid therapy. Therefore, intubation was performed and mechanical ventilation was initiated. The patient developed a septic shock and renal failure with a glomerular filtration rate of 27.5 mL/min/1.73 m 2 ; therefore, two hemodiafiltration sessions were started. The bronchoalveolar lavage revealed erythematous lesions in the bronchial tree and abundant purulent secretions and erosions in the bronchial mucosa, with a cavitary lesion in the right bronchial tree. The bronchoalveolar lavage samples were used to isolate Trichosporon asahii, Klebsiella pneumoniae, and Pseudomonas aeruginosa carbapenemase class A . Matrix-assisted laser desorption/ionization–time of flight (MALDI-TOF) Biotyper mass spectrometry and polymerase chain reaction (PCR) molecular identification were performed. This case report suggested that patients with severe COVID-19 pneumonia, with or without comorbidities, are more susceptible to opportunistic infections.